KARAKTERISTIK FISIKOKIMIA KUE SEMPRONG DARI CAMPURAN TEPUNG PISANG GOROHO (Musa acuminate, L) DAN TEPUNG SAGU (Metroxylon sago, Rottb) - Memey Elim Uller; Maria F. Sumual; Erny . Nurali (Universitas Sam Ratulangi, 2017)
ABSTRACTThis research were aimed to evaluate the sensory characteristics of eggroll cookies acceptable to the panelists, to determine the physicochemical characteristics and to obtain the mostpreferable formulas of goroho plantain flour and sago flour. This study used Completely Randomized Design (RAL) with treatment A (100% goroho plantain flour), B (75% gorohoplantain flour and 25% sago flour), C (50% goroho plantain flour and 50% sago flour), D (25% goroho plantain flour and 75% sago flour) and E (100% sago flour). Parameters analyzed were sensory, fracture force and chemical composition i.e moisture, ash, fat, protein and carbohydrate. Results showed that eggroll cookies made of 75% goroho banana flour and 25% sago flour were the most preferred cookies which have a fracture force of 24 mm/g/sec and chemical composition of 4.04% moisture, ash 1.7%, fat 27.49%, 3.35% protein, and 63.42% carbohydrate.Keywords: eggroll cookies, goroho plantain flour, sago flour